Oxidation behavior and microstructural decomposition of Ti-6Al-4V and Ti-6Al-4V-1B sheet. (November 2016) - Brice, D.A.; Samimi, P.; Ghamarian, I.; Liu, Y.; Brice, R.M.; Reidy, R.F.; Cotton, J.D.; Kaufman, M.J.; Collins, P.C.
Highlights: Weight change measurements show that the addition of boron to the alloy reduces oxygen pick up. Oxygen ingress depleted β-Ti phase near the metal surface and developed α-case. For the oxidation temperature of 950 °C the precipitation of α2 (Ti3 Al) was recorded in SEM. TEM compositional measurements show Al and V enrichment of α2. . Abstract: A direct comparison between the oxidation behavior of Ti-6Al-4V and Ti-6Al-4V + 1B has been conducted to elucidate whether the addition of boron to Ti-6Al-4V impacts the oxidation behavior. Industrially prepared sheet of Ti-6Al-4V and Ti-6Al-4V + 1B were oxidized at temperatures between 650 and 950 °C for holding times of 25 and 50 h. Weight-gain measurements and characterization of surface and near-surface microstructures showed that the addition of 1 wt% B increased the material's oxidation resistance. Additionally, the ingress of oxygen tends to decrease the solubility of other alloying species in α-Ti and leads to the formation of a distinctive and atypical microstructure with a distinct morphology.